2000
DOI: 10.3109/00016340009169191
|View full text |Cite
|
Sign up to set email alerts
|

Second lower genital tract squamous cell carcinoma following cervical cancer: A clinical study of 46 patients

Abstract: Treatment outcome in patients with second lower genital tract carcinoma is unsatisfactory due to poor feasibility of another definite treatment after previous radical surgery and/or radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…No prognostic factors for survival were identified. 2 Misdiagnosis of second malignancies may occur, as happened in the case of postirradiation bladder cancer reported by Nimmanon and Ruengpoka, in which malignant fibrous hystiocytoma of the urinary bladder that occurred 15 years after radiation therapy for cervical cancer, was misdiagnosed initially as high grade urothelial carcinoma. 11 Endometrial cancers are usually diagnosed by performing endometrial biopsy or fractional curettage for postmenopausal bleeding.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…No prognostic factors for survival were identified. 2 Misdiagnosis of second malignancies may occur, as happened in the case of postirradiation bladder cancer reported by Nimmanon and Ruengpoka, in which malignant fibrous hystiocytoma of the urinary bladder that occurred 15 years after radiation therapy for cervical cancer, was misdiagnosed initially as high grade urothelial carcinoma. 11 Endometrial cancers are usually diagnosed by performing endometrial biopsy or fractional curettage for postmenopausal bleeding.…”
Section: Discussionmentioning
confidence: 93%
“…1 A retrospective analysis of 46 second cancers of the lower genital tract reported the mean age of patients at the time of diagnosis of the second cancer to be 63 years, and the median time for their diagnosis or discovery to be 206 months. 2 Estimating the risk of all second cancers among 104,760 one year survivors of cervical cancer, it was found that the overall risk was increased significantly. And it was increased further when compared with those who did not receive radiation.…”
Section: Discussionmentioning
confidence: 99%
“…Modalities of treatment for vaginal radiation-induced carcinoma were quite different based on radical surgery or exenteration, radiotherapy, or palliative chemotherapy. 13,15,21 Senkus et al 21 reported that the intent of treatment for a secondary tumor and the stage of the secondary tumor did not represent significant prognostic factors. 21 In fact, it is difficult to assess precisely the …”
Section: Discussionmentioning
confidence: 98%
“…In a retrospective study conducted by Senkus et al 21 concerning 35 radiation-induced squamous cell carcinoma of the vagina or the vulva, 24 tumors were located within the high dose volume and 11 within the scattered irradiation area. The time span between pelvic irradiation and vaginal/ vulvar cancers ranged from 79 to 402 months (median 219 months).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation